ANALISIS MINAT DAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DALAM PENGGUNAAN MEDIA CHROMEBOOK DI SMAI SABILUL HUDA - Hanafi; Imam Syafi’i; Yetti Hidayatillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of Chromebook media usage on students' interest and motivation in learning Pancasila Education subjects at SMAI Sabilul Huda, Ganding District. The method used is a quantitative approach with a descriptive survey design. Data were collected through structured questionnaires distributed to student samples. The results showed that the use of Chromebooks has a positive and significant effect on increasing students' interest and motivation in learning. This finding is supported by statistical analysis showing a positive correlation between the frequency of Chromebook use and the level of interest and motivation in learning. However, the discussion of the results still considers qualitative aspects to provide a deeper understanding of student experiences. The implication of this study is the importance of integrating appropriate technology in learning to improve student engagement and performance.